Financial modelling in commodity markets - Fanelli, Viviana (Boca Raton, FL : CRC Press, 2020)
Financial Modelling in Commodity Markets provides a basic and self-contained introduction to the ideas underpinning financial modelling of products in commodity markets. The book offers a concise and operational vision of the main models used to represent, assess and simulate real assets and financial positions related to the commodity markets. It discusses statistical and mathematical tools important for estimating, implementing and calibrating quantitative models used for pricing and trading commodity-linked products and for managing basic and complex portfolio risks. Key features: Provides a step-by-step guide to the construction of pricing models, and for the applications of such models for the analysis of real data Written for scholars from a wide range of scientific fields, including economics and finance, mathematics, engineering and statistics, as well as for practitioners Illustrates some important pricing models using real data sets that will be commonly used in financial markets
OCLC-licensed vendor bibliographic record.
Keywords: Finance -- Mathematical models; Commodity exchanges; BUSINESS & ECONOMICS / Finance